(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
The aim of the present research work is set on how AI tools influence grammar, vocabulary, fluency, and comprehension in the learning of the English language. It goes on to discuss the ways these AI technologies improve learning outcomes in different educational contexts and their implications for educators and policymakers. Case study methodology will be used with data from three diverse learning contexts in Iraq , city high school, rural community center, and university ESL program. The language proficiency scores at pre- and post-intervention points were taken to measure the changes, supported by qualitative findings of the measures of user engagement and user satisfaction surveys. Conclusions regarding the improvement on an observed basis will be determined by statistical tests in a valid sample. The results indicated a tremendous improvement in the language skills of all case studies. Grammar proficiency improved by 33.3% in urban high schools, 55.6% in rural community centers, and 30.8% at university ESL programs, while vocabulary retention increased by 50%, 62.5%, and 45.5%, respectively (p < 0.05). There were also significant increases in fluency and comprehension, but the rural learners’ relative gain was highest, being so easy to access and adapt for AI-powered tools. Satisfaction surveys indicated a very high level of satisfaction among users, with mean scores for perceived ease of use ranging from 4.0 to 4.7 on a 5-point Likert scale. Several issues that have been raised concern infrastructure limitations and the need for cultural relevance. AI tools greatly enhance the learning process of English through personalized, interactive, and efficient learning experiences. Although much potential exists in helping to bridge the gap in educational inequities, these are associated with significant challenges in access to technology and ethics. Long-term impacts, hybrid learning models, and strategies for equity assurance in AI implementation are some aspects that need future research.